Evaluation of chemokines in gingival crevicular fluid in children with band and loop space maintainers: A clinico-biochemical study - Naveen Kommineni Kumar; Veera Kishore Kasa Reddy; Prathyusha Padakandla; Harshini Togaru; Swathi Kalagatla; Vinay Chand M Reddy (Wolters Kluwer Medknow Publications, 2016)
Background: Chemokines are pro-inflammatory cells that can be induced during an immune response to recruit cells of the immune system to a site of infection. Aim: This study was conducted to detect the presence of chemokines, macrophage inflammatory protein-1α (MIP-1α), and 1β (MIP-1β) and estimate their levels in gingival crevicular fluid (GCF) in children with band and loop space maintainers. Materials and Methods: MIP-1α and MIP-1β levels were estimated in GCF samples from twenty healthy children and twenty children with band and loop space maintainers. Periodontal status was evaluated by measuring gingival index, plaque index, and Russell's periodontal index. The GCF samples were quantified by ELISA, and the levels of MIP-1α and MIP-1β were determined. Results: The mean MIP-1α concentrations in healthy children and those with space maintainers were 395.75 pg/µl and 857.85 pg/µl, respectively, and MIP-1β was 342.55 pg/µl and 685.25 pg/µl, respectively. MIP-1α and MIP-1β levels in GCF from children with space maintainers were significantly higher than in the healthy group, and statistically significant difference existed between these two groups. Conclusion: MIP-1α and MIP-1β can be considered as novel biomarkers in the biological mechanism underlying the pathogenesis of gingival inflammation in children with space maintainers.